Literasi Lingkungan dan Perilaku Pro-Lingkungan Pekerja Tambang Batubara: Analisis Knowing-Doing Gap dalam Implementasi ISO 14001:2015 - Febrian Febrian; Nurhasan Syah; Mulya Gusman; Syafrijon Syafrijon (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the knowing-doing gap in environmental literacy among coal mine workers implementing ISO 14001:2015 at PT XYZ, South Sumatra. Despite being ISO 14001 certified, the gap between environmental knowledge and actual pro-environmental behavior remains a critical challenge in sustainable mining. Using a mixed-methods design, researchers surveyed 24 workers through questionnaires, semi-structured interviews, field observations, and document analysis. Environmental literacy was assessed through three dimensions: knowledge, attitudes, and behavior, based on the McBeth & Volk framework. Quantitative data were analyzed using descriptive statistics (SPSS 25), while qualitative data were analyzed through thematic analysis. The results indicate high environmental literacy knowledge (83% understand the policy) and positive attitudes (>65% agree with environmental responsibility), but low consistent behavior with only 42% attending regular training and 38% participating in reclamation programs, indicating a 41% gap. Key barriers include productivity pressures, inflexible training schedules, the absence of an incentive system, and weak management role models. ISO 14001:2015 effectively enhances the knowledge dimension through policy dissemination and audits, but fails to drive behavioral change without complementary organizational mechanisms. This research contributes to a conceptual model that integrates individual literacy with organizational determinants, demonstrating that sustainable mining requires systemic interventions beyond administrative compliance